Overexpression of Fibrinogen in ApoE*3-Leiden Transgenic Mice Does not Influence the Progression of Diet-Induced Atherosclerosis - Rezaee, F.; Gijbels, M. J.; Offerman, E. H.; van der Linden, M.; De Maat, M. P. M.; Verheijen, J. H. (Thrombosis and Haemostasis, 2002)
Although many epidemiological studies have shown an association between hyperfibrinogenemia and atherosclerosis, it is not established whether elevated fibrinogen has an etiological role in the pathogenesis or is only a reflection of the ongoing disease.We have studied the contribution of fibrinogen to the development of atherosclerosis in atherosclerosis-prone ApoE*3-Leiden mice that have been cross-bred with transgenic mice overexpressing fibrinogen. Genetic compound offspring were used to evaluate the progression of atherosclerotic lesions after being fed an atherogenic diet for 7 weeks. It was observed that the lesion area of the plaques as well as the severity of the lesions in the aortic valve was comparable in control single transgenic ApoE*3-Leiden mice and in double transgenic apoE*3-Leiden mice overexpressing fibrinogen. No thrombus or fibrin deposition was observed in atherosclerotic lesions in either group of mice.These results indicate that elevated plasma fibrinogen concentrations in ApoE*3-Leiden transgenic mice do not affect the progression of diet-induced atherosclerotic lesions.
Keywords: Atherosclerosis; fibrinogen overexpression; transgenic mouse